2020
DOI: 10.3390/su12041356
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Food Waste and Biochar In-Vessel Co-Composting

Abstract: As bulking agents (BA) affect the composting process, this work examined the impact of combinations of different organic components in order to obtain an efficient co-substrate for food waste (FW) in-vessel composting. To boost the occurrence of microorganisms inhabiting the compost, mature compost was firstly coupled with wheat straw, added to FW, and considered as a control (BC0). Then, two trials (BC10, BC20) including 10% and 20% of biochar were monitored. The results indicated that the temperature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…These were corrected at a later stage and regulated in the range of 20-30 for different feedstocks by the addition of CM for anaerobic digestion and GW for thee composting process as co-substrates [61]. As the presence of minor elements is crucial for the microorganism communities, some micro-and macro-elements were identified [62]. Copper (Cu), nickel (Ni), and zinc (Zn) were detected in varying quantities, with Zn recording the highest quantities in the different substrates.…”
Section: Characterization Of the Selected Biowastementioning
confidence: 99%
“…These were corrected at a later stage and regulated in the range of 20-30 for different feedstocks by the addition of CM for anaerobic digestion and GW for thee composting process as co-substrates [61]. As the presence of minor elements is crucial for the microorganism communities, some micro-and macro-elements were identified [62]. Copper (Cu), nickel (Ni), and zinc (Zn) were detected in varying quantities, with Zn recording the highest quantities in the different substrates.…”
Section: Characterization Of the Selected Biowastementioning
confidence: 99%
“…As the ratio between NH 4 + and NO 3 − ; the nitri cation index (NI) is considered as an indicator of the compost's stability (Chaher et al, 2020a), it was monitored during the composting process to evaluate the nitrogen transformation reactions. Figure 6 showed that, during the thermophilic phase, NI of the unamended reactor (A1) was considerably higher than the amended one (A2 Accomplishing the cooling phase, NI for both of A1 and A2 was progressively dropping to reach approximatively 3 at the end of the process.…”
Section: Nitri Cation Index (Ni) and Respiration Activity (At4)mentioning
confidence: 99%
“…Indeed, the signi cant amounts of metal components which marked A2 were predicted by the initial rate of HMs provided by the digestate as described in Table 1. However, despite the remarkable content in terms of HMs, A2 met all the laws applicable in several countries and it was classi ed as a Class B biofertilizer in reference to the German Standards (Chaher et al, 2020a). Additionally, Table 4 shows that the compost gathered from A1 was categorized as Class A based on the German limits and illustrated that both amended and unamended reactors generated high quali ed end products.…”
Section: Effect Of Digestate Addition On End-product Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, by comparing temperature trends, the modi ed reactor speeded up the thermophilic phase and expanded its duration (15 days) which emphasised the effectiveness of digestate addition. It might be also due to the in uence the introduction of biochar to anaerobic reactors which played a crucial role to enhance the AD residue properties by intensifying the microbial activity (Chaher et al 2020a and Suthar 2020). However, assuming that the digestion acquired from AD reactors can be used directly as a soil conditioner, it was clear that pasteurization is mandatory to ensure its puri cation, which is the largest energy consumer in the anaerobic digestion (AD) chain (Liu et al, 2019).…”
Section: Physio-chemical Properties Of the Raw Materialsmentioning
confidence: 99%